Assessing Creativity by Meaning - Kreitler, Shulamith (Advances in Social Sciences Research Journal, 2026)
The paper presents a new approach to the assessment of creativity in terms of the meaning system. A brief presentation of the major constructs of meaning in line with the theory of meaning by Kreitler and Kreitler is followed by the theoretical and empirical considerations that have led to the hypothesis that it would be possible to assess creativity in terms of the meaning system. Three studies are presented briefly describing the meaning variables that were found to differentiate significantly between the more and less creative participants, in different samples of children, and with different measures of creativity used for validating the new meaning-based measure. A set of meaning variables characterizing the more creative children was identified. It was found that the more creative individuals tended to focus both on external and internal reality, on the general and the specific, on the personal-subjective and the interpersonally-shared, and on the present inputs and more distant ones.